An Economic Model Of The Cobalt Market - Gregory Dybalski (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1977)
The purpose of this paper is to illustrate the forecast capability of the econometric model of the cobalt industry1/ as utilized by the Federal Preparedness Agency. Forecasts from this model are illustrated from the premise that the leading producer continues production of cobalt. An alternate forecast is presented where the model structure is altered to reflect the condition where the leading producer leaves the market. All estimations and forecasts presented here are shown for illustrative purposes. The cobalt industry is highly concentrated; one company, owned by the Zaire government, accounts for approximately three-fifths of world production. The cobalt supply outside of Zaire is determined by the level of activity of copper or nickel markets, as cobalt is mined as a by-product of copper or nickel. The demand for cobalt reflects a diversified usage pattern; cobalt is used mainly in heat and corrosion-resistant materials, high- strength materials and permanent magnets. According to 1974 U.S. consumption data superalloys accounted for 22%, magnetic alloys 18%, cutting and wear-resistant materials 13%, and catalyst 7%. Foreign consumption is probably similar in terms of usage categories, but the relative order of the categories is in variance.2/ The Cobalt Model The cobalt model's object is to explain consumption, supply and price movements by utilizing statistically estimated equations. Central to the econometric model is the role of Zaire as the profit-maximizing "dominant firm". Zaire sets the price that is most profitable for itself. The price of cobalt depends on industrial demand, production of other firms, and net exogenous purchases, such as government